Two Phases of Metamorphism in the High-Pressure Schists in Central Inner Mongolia, China: Implications for the Tectonic Transition From Terminal Subduction of the Paleo-Asian Ocean to Continental Collision - Zhang, Jinrui; Tang, Shuang; Wei, Chunjing; Chu, Hang; Xu, Wenliang; Jiang, Ling (Frontiers in Earth Science, 2022)
High-pressure (HP) rocks exhumed from subduction zones usually record much warmer geotherms than numerical modelling results, as their peak mineral assemblages are always modified during the exhumation process. The decompressional metamorphic evolution of HP rocks should be considered carefully if using their P–T records to constrain the thermal structure of a subduction zone. The Ondor Sum Group, known as mélanges containing various high P/T metamorphic rocks in central Inner Mongolia, represents a fragment of subducted oceanic crust in the Early Paleozoic, In this study, the HP schists were newly discovered in the Ondor Sum Group at Airgin Sum in the central Inner Mongolia. The HP schists include a garnet–phengite schist (sample EL01) and a garnet–amphibole schist (sample EL08). The petrography of these rocks and phase equilibrium modelling using THERMOCALC suggest two phases of metamorphism, both of which are characterized by clockwise P–T evolutions involving pre-peak prograde stage, peak-stage, and post-peak decompression stage. The peak P–T conditions of the early-phase metamorphism are constrained by P–T pseudosections to be ~18 kbar/~535 °C for sample EL01 and 18 kbar/~500 °C for sample EL08. The peak P–T conditions of the late-phase metamorphism are constrained by P–T pseudosections to be ~8 kbar/532 °C in EL01 and ~7.0 kbar/495 °C in EL08. Available U–Pb data of zircons from the HP schists and a granodiorite vein using LA–ICP–MS constrain the timing of early-phase HP metamorphism in the early Paleozoic and the late-phase metamorphism supposed to be in the Devonian based on the previous reported ages. The peak P–T conditions for the early-phase metamorphism were high-P/T conditions with a thermal gradient of ~8 °C/km, pointing to a warm oceanic subduction. The overprinting late-phase metamorphism represents medium-P/T conditions with a geothermal gradient of 22–25 °C/km, which we attribute to a collisional thickening process. As a result, we suggest that the HP schists in the Ondor Sum Group represent the terminal stage of subduction of the Paleo-Asian oceanic plate, and that the schists were involved in the continental collision after the closure of the Paleo-Asian Ocean in the Devonian.